Politeness Strategies as Self-Presentation in Laufey’s Podcast Interviews Based on Leech’s Principles - Anindy Fatihah Aulia Illahi; Nur Utami Sari’at Kurniati; Resty Widya Kurniasari (Journal of Cultural Narratives in Digital Society, 2026)
This study examines the use of politeness strategies in Laufey’s utterances in two podcast interviews, Q with Tom Power and Royal Court with Brittany Broski, based on Leech’s Politeness Principle (1983). Grounded in pragmatic analysis, this research examines how politeness functions not only as a linguistic norm but also as a strategic resource for self-presentation in public digital discourse. Using a qualitative descriptive approach, 80 utterances were analyzed, revealing 87 realizations of politeness maxims. The findings show that four of Leech’s six maxims are employed, namely modesty (47 instances), approbation (19), agreement (12), and tact (9). The dominance of the modesty maxim indicates a consistent tendency to minimize self-praise, even when discussing professional achievements. Drawing on Goffman’s framework of self-presentation, these strategies function as forms of impression management, enabling the construction of a controlled, approachable, and professional public persona. This study highlights politeness as a strategic linguistic resource in shaping self-presentation within contemporary podcast discourse.